Stomach Content Analysis and Reproductive Biology of Pangasius polyuranodonFromThe Siak and Kampar Rivers, Riau - Melsa Dwi Yunita; Eddiwan '; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Pangasius polyuranodon is one of freshwater fishes that inhabit the Siak and Kampar Rivers in Riau. Water qualities in those areas are different. Availabillity of food and the success of reproduction are important factors for the fish existence. To understand the stomach content and reproductive biology of this fish, a study has been conducted from October – December 2016.The fish was sampled in the Siak and Kampar Rivers. Fifty fishes were taken from the Siak River and fifty three fishes were collected from the Kampar River. Stomach content of the fish was analyzed as a basis to calculate the Preponderance Index (PI). Fecundity was analyzed using a gravimetric method. Results shown the feed of P. polyuranodonconsist of bivalve, gastropods, insects, crustacean, fish, palm fruit (Elaeis guineensis), fruits, leaves and seeds. The main food of P. polyuranodon in Kampar River was bivalve (74%) and that of the Siak River were insects (55%). All of fishes captured shown trace of developing gonads. During the 4th maturity stage, the main food of P. polyuranodon from the Kampar River was bivalves and that of the Siak River were insects. Based on data obtained, it can be concluded that this fish can be categorized as omnivore, and they tend to choose high content protein and fat feed during gonad development. The ability of fish in consuming fruits indicates that P. polyuranodonisafrugivory fish. Keywords: Pangasius polyuranodon, Feeding Habit, Omnivorous,Frugivory Fish